Molecular Basis for Strain Variation in the Saccharomyces cerevisiae Adhesin Flo11p - Subit Barua (American Society for Microbiology, 2016)
ABSTRACT FLO11 encodes a yeast cell wall flocculin that mediates a variety of adhesive phenotypes in Saccharomyces cerevisiae. Flo11p is implicated in many developmental processes, including flocculation, formation of pseudohyphae, agar invasion, and formation of microbial mats and biofilms. However, Flo11p mediates different processes in different yeast strains. To investigate the mechanisms by which FLO11 determines these differences in colony morphology, flocculation, and invasion, we studied gene structure, function, and expression levels. Nonflocculent Saccharomyces cerevisiae Σ1278b cells exhibited significantly higher FLO11 mRNA expression, especially in the stationary phase, than highly flocculent S. cerevisiae var. diastaticus. The two strains varied in cell surface hydrophobicity, and Flo11p contributed significantly to surface hydrophobicity in S. cerevisiae var. diastaticus but not in strain Σ1278b. Sequencing of the FLO11 gene in S. cerevisiae var. diastaticus revealed strain-specific differences, including a 15-amino-acid insertion in the adhesion domain. Flo11p adhesion domains from strain Σ1278b and S. cerevisiae var. diastaticus were expressed and used to coat magnetic beads. The adhesion domain from each strain bound preferentially to homologous cells, and the preferences were independent of the cells in which the adhesion domains were produced. These results are consistent with the idea that strain-specific variations in the amino acid sequences in the adhesion domains cause different Flo11p flocculation activities. The results also imply that strain-specific differences in expression levels, posttranslational modifications, and allelic differences outside the adhesion domains have little effect on flocculation. IMPORTANCE As a nonmotile organism, Saccharomyces cerevisiae employs the cell surface flocculin Flo11/Muc1 as an important means of adapting to environmental change. However, there is a great deal of strain variation in the expression of Flo11-dependent phenotypes, including flocculation. In this study, we investigated the molecular basis of this strain-specific phenotypic variability. Our data indicate that strain-specific differences in the level of flocculation result from significant sequence differences in the FLO11 alleles and do not depend on quantitative differences in FLO11 expression or on surface hydrophobicity. We further have shown that beads coated with amino-terminal domain peptide bind preferentially to homologous cells. These data show that variability in the structure of the Flo11 adhesion domain may thus be an important determinant of membership in microbial communities and hence may drive selection and evolution.